Use of a Volume Navigation Technique for Combining Real-Time Ultrasound and Contrast-Enhanced MRI: Accuracy and Feasibility of a Novel Technique for Locating Breast Lesions - (:unkn) unknown (AMER ROENTGEN RAY SOC, 2016)
OBJECTIVE. The objective of this study was to evaluate the accuracy of the volume navigation technique for combining real-time ultrasound and contrast-enhanced MRI (CE-MRI) of breast lesions. SUBJECTS AND METHODS. Thirty-eight women with single breast lesions underwent 3-T MRI. A 3.5-minute CE-MRI sequence was used, as was a flexible body coil. Patients underwent imaging in the supine position, with three markers placed on their breasts. Real-time sonographic images were coregistered to the preloaded breast CE-MRI volume by coupling skin markers, with the use of an electromagnetic transmitter positioned next to the subjects. The transmitter detected the spatial positions of the two electromagnetic sensors mounted on the transducer bracket. After this fusion process in 3D space was completed, divergences in the location of the center of each lesion on CE-MRI and ultrasound images were analyzed. RESULTS. The mean lesion size was 17.4 mm on ultrasound and 17.9 mm on MRI, whereas the mean (+/- SD) misalignment of the lesion centers on CE-MRI and ultrasound was 3.9 +/- 2.5 mm on the x-axis (mediolateral view), 3.6 +/- 2.7 mm on the y-axis (anteroposterior view), and 4.3 +/- 2.6 mm on the z-axis (craniocaudal view). No lesion had a misalignment greater than 10 mm on any of three axes. The accuracy of volume navigation was independent of patient age and the lesion size, location, and histopathologic findings (p > 0.05). Intermediate lesions, which had a depth of center of 11-20 mm on ultrasound had a mean misalignment of 2.6 +/- 1.9 mm, compared with 5.5 +/- 2.2 mm for deep lesions, which had a depth of center greater than 20 mm (p = 0.049). CONCLUSION. The volume navigation technique is an accurate method for coregistration of CE-MRI and sonographic images, enabling lesion localization within a limited volume.
Keywords: breast lesion; breast ultrasound; MRI; volume navigation technique; TARGETED ULTRASOUND; CANCER; GUIDELINES; FUSION; IMAGE; WOMEN